Interfacially Bridging Covalent Network Yields Hyperstable and Ultralong Virus‐Based Fibers for Engineering Functional Materials. Issue 41 (13th August 2020) - Zhou, Kun; Zhou, Yihao; Yang, Hongchao; Jin, Huile; Ke, Yonggang; Wang, Qiangbin
Abstract: We present a strategy of interfacially bridging covalent network within tobacco mosaic virus (TMV) virus‐like particles (VLPs). We arranged T103C cysteine to laterally conjugate adjacent subunits. In the axis direction, we set A74C mutation and systematically investigated candidate from E50C to P54C as the other thiol function site, for forming longitudinal disulfide bond chains. Significantly, the T103C‐TMV‐E50C‐A74C shows the highest robustness in assembly capability and structural stability with the largest length, for TMV VLP to date. The fibers with lengths from several to a dozen of micrometers even survive under pH 13. The robust nature of this TMV VLP allows for reducer‐free synthesis of excellent electrocatalysts for application in harshly alkaline hydrogen evolution. Abstract : A strategy to interfacially bridge a covalent network within tobacco mosaic virus (TMV) virus‐like particles (VLPs) is presented. T103C‐TMV‐E50C‐A74C shows the highest robustness in assembly capability and structural stability with the largest length for a TMV VLP to date. The robust nature of this TMV VLP allows for reducer‐free synthesis of excellent electrocatalysts for application in harshly alkaline hydrogen evolution.